Therapeutic Potential of Umbilical Cord Mesenchymal Stromal Cells Transplantation for Cerebral Palsy: A Case Report. (3rd March 2013) - Wang, Liming; Ji, Haijie; Zhou, Jianjun; Xie, Jiang; Zhong, Zhanqiang; Li, Ming; Bai, Wen; Li, Na; Zhang, Zijia; Wang, Xuejun; Zhu, Delin; Liu, Yongjun; et al.
Abstract : Cerebral palsy is the most common motor disability in childhood. In current paper, we first report our clinical data regarding administration of umbilical cord mesenchymal stem cells (MSCs) transplantation in treatment of cerebral palsy. A 5-year-old girl with cerebral palsy was treated with multiple times of intravenous and intrathecal administration of MSCs derived from her young sister and was followed up for 28 months. The gross motor dysfunction was improved. Other benefits included enhanced immunity, increased physical strength, and adjusted speech and comprehension. Temporary low-grade fever was the only side effect during the treatment. MSCs may be a safe and effective therapy to improve symptoms in children with cerebral palsy.